Serum hyaluronan as a marker reflecting the severity of cirrhosis and portal hypertension in postoperative biliary atresia - Chongsrisawat V. (2014)
The majority of patients with biliary atresia (BA) develop progressive liver disease and serious complications of portal hypertension, including esophageal varices and ascites, despite successful Kasai operation. The aim of this study was to evaluate whether serum hyaluronan (HA) reflects the severity of cirrhosis and its complications in patients with postoperative BA. Fifty-four postoperative BA patients aged 1 to 19 years were recruited into this study. Serum HA was determined by ELISA-based assay, and serum HA levels were compared among groups of patients according to Child's classification as well as the presence of esophageal varices and ascites. Mean serum HA concentration was significantly increased in patients with Child C (534.35 ± 573.02 ng/ml) in comparison to patients with Child B (97.67 ± 104.22 ng/ml, p = 0.002) and Child A (36.27 ± 71.41 ng/ml, p < 0.001). Mean serum HA concentration was also significantly higher in patients who had ascites or esophageal varices than in those who did not suffer from these complications. Furthermore, patients who had variceal hemorrhage had significantly higher mean serum HA levels than those without bleeding. Thus, serum HA levels may reflect the severity of cirrhosis and its complications, and may be useful in monitoring the clinical outcomes of patients with postoperative BA. © Springer-Verlag 2004.